Representasi Ikhtiar dan Tawakal dalam Kisah Nabi Ayyub AS Analisis Teori Kasb Al-Asy’ari - Pasya Tiara R; Vina Nailatul Izzah; Suci Rahmanda; Zahra Nur Asyifa; Dadan Firdaus (Indo Publishing, 2026)
This study examines the representation of ikhtiar (human effort) and tawakal (trust in Allah) in the story of Prophet Ayyub AS through the perspective of Abu al-Hasan al-Ash’ari’s theory of kasb. The research is motivated by the tendency to separate human effort from reliance on God, which often leads to an incomplete understanding of Islamic teachings. This study aims to describe the concept of ikhtiar and tawakal within the framework of kasb theory and analyze their representation in the story of Prophet Ayyub AS, including their implications for inner peace. Using a qualitative approach and library research method, data were collected from Qur’anic verses related to Prophet Ayyub AS and supported by classical and contemporary literature. The findings reveal that Prophet Ayyub AS demonstrated a balance between effort and submission to Allah through patience, prayer, obedience, and perseverance during prolonged suffering. The study also shows that the theory of kasb provides a theological explanation of the relationship between human responsibility and divine will. It concludes that inner peace is achieved through the harmony between sincere effort and trust in Allah. This study contributes to enriching Islamic theological discourse and offers relevant guidance for facing challenges in modern life.